Student learning difficulties in social science subjects at IRA Private Madrasah Tsanawiyah Medan - Nasution, Mega Sara; Perkasa, Ripho Delzy (CAHAYA PENDIDIKAN, 2024)
The purpose of this study was to investigate the various learning difficulties faced by students in social studies subjects at MTs Swasta IRA Medan. To achieve these objectives, research data were collected through the methods of observation, interviews, and documentation. The research subjects in this study were social studies teachers and students in grades VII, VIII, and IX at MTs IRA Medan. Data analysis in this study includes data collection, data presentation, and conclusion drawing. The results showed that the learning difficulties experienced by students were due to the lack of understanding of student concepts, lack of interest in social studies subjects, the absence of a relevant relationship between the material taught and daily life and lack of support from parents. An unsupportive learning environment also plays a major role in the learning difficulties faced by students.